Tilkoblings- og afkoblingsstrategier i dansk udenrigspolitik: Udvikling og tendenser i de danske udenrigspolitiske doktriner - Pedersen, Rasmus Brun (Politik, 2015)
This paper investigates the developments and changes in the Danish foreign policy doctrines from 1914-2014 in order to study the relative importance of two underlying ideologies that have guided the Danish strategic culture. It is argued that determinism and internationalism has traditionally constituted the Danish small state identity, which have led to an understanding of a dualistic strategic culture. e argument is that this dualism after the end of the Cold War has been replaced with a one stringed internationalism after the end of the cold war where the introduction of international activism and active internationalism can be seen as a broad ‘opting in’ strategy to the international system.